(untitled) (Revista de Ciências Agroveterinárias, 2018)
Permanent Preservation Areas (PPA), especially around river banks, springs and lakes, contribute significantly to the quality of the hydrological cycle. Environmental valuation is considered an important methodological tool to subsidize decision-making for the natural resources use. This study aimed to quantify the area of PPA’s in springs and margins of water courses, before and after the change in the Forest Code; and to estimate the economic value of priorities PPA’s. The study was conducted in the Passaúna River Watershed, located in the city of Curitiba. The GIS data were made available by the Water Institute of Paraná State. The "opportunity cost" method was used for economic valuation combined with priorities areas. Using the limits of the new Forest Code (2012) there may be a reduction of 1,077.1 ha in PPA’s around river banks, springs and lakes. The agricultural area is predominant, representing 46.11% of the total area. It was identified 204.9 and 872.2 hectares areas as high and low priority areas respectively. The estimated economic value for the maintenance of these areas is R 945.00 ha/year. It is concluded that the presented map and the environmental valuation are an important reference for decision-making by public managers, as well for the public policies implementation, as payment for ecosystem services, which reward and encourage rural producers to conserve forest areas with important environmental functions.